Show that x-2 x+3 x-7 are factors of x3-6x2+13x+42
Answers
Answered by
1
please correct ques i think ques is
x3 - 6x2 - 13x + 42
then put x = 2 , -3 , 7
if f(2) = 0
f(-3) = 0
f(7 ) = 0
then x-2 , x+3 and x-7 will be factors of f(x)
x3 - 6x2 - 13x + 42
then put x = 2 , -3 , 7
if f(2) = 0
f(-3) = 0
f(7 ) = 0
then x-2 , x+3 and x-7 will be factors of f(x)
Answered by
5
Answer:
hope it helps you please mark it as brainliest
Attachments:
Similar questions
Math,
7 months ago
Math,
7 months ago
Physics,
1 year ago
Social Sciences,
1 year ago
Math,
1 year ago